Space Pattern of the Mortality in Germany and the Development Tendencies Between 1998 and 2004 - Behrendt, Holger (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
The subject of the present study is based on an analysis by regions with regards to the mortality in Germany, divided into the “old” and “new” federal countries between 1998 and 2004. The results show that the new countries have caught up with the situation of mortality compared to the old countries, the process being however more distinct for women than for men. The equalising process of the mortality situation, observed in small regions, is connected with an increase in disparities in West Germany, while these are decreasing in Eastern Germany. The different structure of settlements clearly shows deviations between the mortality situation in the old and new countries. The urbanised regions in the old countries have the highest life expectancy from birth, while life expectancy in the new countries reduces from the agglomeration areas to the rural regions. Only the core cities in the agglomeration areas in the new countries have a higher life expectancy from birth compared to the old countries. The differentiation in socio-economic circumstances of the mortalities shows that the more the gradient of socio-economic circumstances varies, the higher are the regional differences in mortality. Using the indicator “avoidable deaths” as an output indicator, it is possible to show that medical precautions and care, during both the interpretation of the regional differences as well as during the examination of the development over time of the mortality, build an important and independent explanation.